SISTEM INFORMASI INVENTORY BARANG BERBASIS WEB PADA PT. SERVVO FIRE INDONESIA - AHMAD SAEFUL MAKKI; Deanna Durbin Hutagalung (CV. Multi Kreasi Media, 2022)
PT Servvo Fire Indonesia is a manufacturer of clean, safe and highly capable Light Fire Extinguishers (APAR) to transmit class B and C fires produced by flammable liquids and electricity for portable units using lightweight, rust-resistant tubes and equipped with non-static static funnels. conductive with the best Fire Alarm System in Indonesia that has been certified by SNI. PT. Servvo Fire Indonesia is the winner of SNI in 2018 and 2019, which is the highest award from the government, the National Quality Award (SNI AWARD).